METHODOLOGY AND HARDWARE FOR DETERMINING THE FORCE REQUIRED TO MOVE THE PLUNGER ROD OF A DISPOSABLE SYRINGE - M. G. Kiselev; V. L. Gabets; S. G. Monich; V. A. Petrov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The purpose of the article is to describe the methodology and hardware for determining the force required for the movement of the plunger rod of a single-use syringe. The measurement method is used to obtain new experimental data. We first-ever obtained the oscillograms of force variation required to move the plunger rod of test syringes and found that, compared to a two-component, three-component syringe is characterized by significantly smaller values of the effort required for the plunger rod to move. So, when it moves without using water, the F value at the beginning of the suction stage is 1.5 times less than that of a two-component syringe and 2.4 times less at the extrusion stage. The use of water increases the force required to move the rod-piston of the test syringes. Thus, for a two-component syringe the force at the suction stage without using water was 4.5 N and 5.5 N – at the extrusion stage, and with the use of water, the values of these forces, respectively, increased to 6.5 and 6 N. For a three-component syringe without water, the plunger rod displacement force at the suction stage was 2.9 N and at the extrusion stage – 2.3 N, and with water the values of these forces increased to 3.7 and 2.9 N, respectively. The device developed makes it possible to conduct comprehensive studies of the effect of the type of syringe, its capacity, the speed of movement of the plunger rod, the duration of the stop between liquid suction and extrusion stages and other parameters on the amount of forces required to move the plunger rod of the syringe. This will allow you to justify the conditions and the normalized value of the force (or forces) required for the movement of the plunger rod when testing syringes by this indicator.